Blood parasites in passerine birds from the Brazilian Atlantic Forest Hemoparasitos em passeriformes da Mata Atlântica Brasileira - Fabiane Sebaio; Érika Martins Braga; Felipe Branquinho; Alan Fecchio; Miguel Ângelo Marini (Revista Brasileira de Parasitologia Veterinária, 2012)
Parasites may lead bird species to extinction, affect host temporal and spatial population dynamics, alter community structure and alter individuals’ social status. We evaluated blood parasite prevalence and intensity according to bird families and species, among 925 birds that were caught in 2000 and 2001, in the Atlantic Forest in the State of Minas Gerais, Brazil. We applied Giemsa staining to thin blood smears, to detect blood parasites. The birds (n = 15.8%) in 11 families, were infected by at least one parasite genus, especially Muscicapidae (28.3%) and Conopophagidae (25%). Among the 146 infected birds, Plasmodium was detected in all bird families and had the highest prevalence (54.8%). Trypanosoma, Haemoproteus and microfilaria had lower prevalence rates (23.3, 23.3 and 2.1%, respectively). Birds caught during the rainy season were more infected than birds caught during the dry season. The overall low prevalence of blood parasites in birds is similar to the patterns found elsewhere in the Neotropical region. Parasitos podem levar espécies de aves à extinção, afetar as dinâmicas temporais e espaciais dos hospedeiros, alterar a estrutura de comunidades e o status social de indivíduos. Avaliou-se a prevalência e a intensidade de parasitos em famílias e espécies de 925 aves capturadas, entre 2000 e 2001, na Mata Atlântica de Minas Gerais. Foram coradas com Giemsa extensões de sangue para detectar parasitos hematozoários. As aves (n= 15,8%) 11 famílias estavam infectadas por pelo menos um gênero de parasito, especialmente Muscicapidae (28,3%) e Conopophagidae (25%). Entre as 146 aves infectadas, Plasmodium foi detectado em todas as famílias e possuiu a maior prevalência (54,8%). Trypanosoma,Haemoproteus e microfilaria possuíram baixas prevalências (23,3, 23,3 e 2,1%, respectivamente). Aves capturadasdurante a estação chuvosa estavam mais infectadas do que aves capturadas durante a estação seca. A baixa prevalência geral de parasitos do sangue das aves é semelhante aos padrões encontrados em outras localidades da região Neotropical.